Apakah Penetapan Kantor Akuntan Publik Dipengaruhi oleh Kepemilikan Perusahaan dan Manajemen Laba? - Bahtiar Effendi (STATERA: Jurnal Akuntansi dan Keuangan, 2021)
This study aims to analyze the effect of company ownership and earnings management on the establishment of a public accounting firm in property & real estate companies listed on the Indonesia Stock Exchange. The population of this study were 187 property & real estate companies for the period 2016-2018. The samples were selected based on purposive sampling criteria with a quantitative method with a descriptive approach. Based on the purposive sampling method, obtained a sample of 42 companies with a total unit of analysis of 126 data obtained from 3 years of observation. This study uses secondary data obtained from financial statement data and annual reports of publicly traded companies listed on the Indonesia Stock Exchange. By using logistic regression analysis as research data analysis, it is found that company ownership and earnings management have a negative and insignificant effect on the determination of the Public Accountant Firm.